Unsettling the Gendered Power Paradigm: Discomfort, Dissonance and Dissention among Women in Local Government - McGregor, Catherine; Clover, Darlene (Canadian Journal of Education/Revue canadienne de l’éducation, 2011)
Despite decades of efforts to achieve gender equity in political life, women remain under-represented in nearly all levels of government. In this paper, we explore the experiences offered by women who have been elected to local government in the province of British Columbia, Canada, to illustrate the persistence of gendered discourses and patriarchal practices within political systems. Drawing upon Bashevkin's (2009) recent discussion of how women's political roles are undermined through the discomfort equation, we consider how feminist, adult education offers the potential for creating critical spaces that will support women's greater inclusion in local government. Keywords: feminist adult education, political learning, gender, politics